Student Worksheet Model Learning Cycle 7E to Practice 4C Skills Learners - Mumtaza, Nazifa; Agustinaningsih, Wiwik (FKIP Universitas Lampung, 2023)
Abstract: Students' 4C skills cannot be trained properly because there are no 7E learning cycle model worksheets available on temperature and heat. So students still have difficulty understanding abstract concepts in the material. The aim of this research is to determine students' 4C skills after using the 7E learning cycle model worksheet. The development method used is Research and Development (R&D) with a 4D model (define, design, develop and disseminate). The participants in this research consisted of 2 physics education lecturers and 1 psychology lecturer as validators, as well as 30 class XI MIPA students at MAN 3 Amuntai. The instruments of this research are validity questionnaires, pretest-posttest questions, communication and collaboration self-assessment sheets, and creative thinking observation sheets. 4C skills after using the 7E learning cycle model worksheet, namely critical skills obtained N-gain, namely 0.54% in the